Spain in Current German Travel Novels - Bies, Andrea (Revista de Filología Alemana, 2021)
Depictions of Spain in contemporary German travel novels represent an area that has hardly been researched to date. Therefore, this study analyses five novels of different genres published since the turn of the millennium, which are dedicated to the experiences of German travellers in Spain. Their images of Spain are produced on two levels: the imaginary and the actual experience of space, whereby the great discrepancy between these two levels leads to disappointment. Through various narrative techniques the characters are exposed as naive and their mostly negative images of Spain as a mirror of their own failure. In addition, Spanish stereotypes are also questioned.
Keywords: Depiction of Spain; Travel Novel; German Contemporary Literature